A standardized bark extract of Pinus pinaster Aiton (Pycnogenol®) attenuated chronic obstructive pulmonary disease via Erk-sp1 signaling pathway. (24th December 2016) - Shin, Na-Rae; Ryu, Hyung-Won; Ko, Je-Won; Park, Ji-Won; Kwon, Ok-Kyoung; Oh, Sei-Ryang; Kim, Jong-Choon; Shin, In-Sik; Ahn, Kyung-Seop
Abstract: Ethnopharmacological relevance: A standardized bark extract of Pinus pinaster Aiton (Pycnogenol ® ; PYC) used as an herbal medicine to treat various diseases in Europe and North America. Aim of the study: This study evaluates the ability of PYC to inhibit chronic obstructive pulmonary disease (COPD) in the cigarette smoke extract (CSE)-stimulated human airway epithelial cell line NCI-H292 and in a cigarette smoke (CS) and lipopolysaccharide (LPS)-induced mouse model. Methods: To induce COPD, the mice intranasally received LPS on day 4 and were exposed to CS for 1 h per day (total eight cigarettes per day) from days 1–7. The mice were administered PYC at a dose of 15 mg/kg and 30 mg/kg 1 h before CS exposure. Results: In the CSE-stimulated NCI-H292 cells, PYC significantly inhibited Erk phosphorylation, sp1 expression, MUC5AC, and pro-inflammatory cytokines in a concentration-dependent manner, as evidenced by a reduction in their mRNA levels. Co-treatment with PYC and Erk inhibitors markedly reduced the levels inflammatory mediators compared to only PYC-treatment. In the COPD mice model, PYC decreased the inflammatory cell count and the levels of pro-inflammatory cytokines in the broncho-alveolar lavage fluid compared with COPD mice. PYC attenuated the recruitment of inflammatory cells in the airways and decreased the expression levels of Erk phosphorylation and sp1. PYC also inhibited the expression of myeloperoxidase and matrix metalloproteinases-9 in lung tissue. Conclusion: Our results indicate that PYC inhibited the reduction in the inflammatory response in CSE-stimulated NCI-H292 cells and the COPD mouse model via the Erk-sp1 pathway. Therefore, we suggest that PYC has the potential to treat COPD. Graphical abstract: